The Influence of Corporate Taxes on Pricing and Capital Structure in Property-Liability Insurance - Gatzert, Nadine; Schmeiser, Hato (Insurance Mathematics & Economics, 2008)
A change in the corporate tax level can have a significant impact on rate making and capital structure for insurance companies. The purpose of this paper is to study this effect on competitive equity-premium combinations for different asset and liability models while retaining a fixed safety level. This is a crucial consideration as a change in the tax rate leads, in general, to a different risk of insolvency. Hence, fixing the safety level serves to isolate the effect of taxes without shifting the insurer's risk situation whenever taxes are varied. The model framework includes stochastic assets as well as stochastic claims costs. We further compare the results for liability models with and without a jump component. Insurance rate making is conducted using option pricing theory.
WiSo-Import:2015-03-26:1372
Keywords: Property-liability insurance; Corporate taxation; Contingent claims valuation